Open Selection for Primary High Leadership Positions at BKPSDM, Solok Selatan Regency - Ilahi, Muhammad Riski; Putera, Roni Ekha; Aryani, Ria (Journal of Public Administration and Government, 2024)
The open selection for Pratama high leadership positions (JPT Pratama) in South Solok Regency has used a well-designed selection mechanism/stage, but in reality, this open selection does not necessarily produce officials who are truly competent in their fields and good at leadership. This is proven by the existence of officials who were demoted from their positions prematurely. So, how is the open selection for JPT Pratam in South Solok Regency? This research uses qualitative methods with snowball sampling techniques to determine research informants. This research shows that the preparation mechanism for the Selection of High Leadership Positions in the South Solok Regency is based on Permenpan-RB Number 15 of 2019. BKPSDM South Solok Regency categorizes preparation into two forms, namely technical preparation and substantive preparation. The implementation of the JPT Pratama Open Selection in South Solok Regency was carried out transparently. However, during the implementation of the JPT Pratama open selection, it was also found that there was a lack of synchronization between the timing stated in the announcement and the actual time when it occurred. The monitoring and evaluation carried out by BKPSDM does not highlight the unsynchronization of the schedule, but rather the monitoring and evaluation carried out by KASN. Apart from that, Monitoring-evaluation also involves assessing the performance of officials selected through the JPT Pratama Open Selection, the results of whose recommendations can be realized in the form of mutations.